Language Presentation of Characters’ Sleeping State A.P. Chekhov’s «Drama on Hunting» (Proceedings of Southern Federal University. Philology, 2017)
Li Kho (Rostov-on-Don, Russian Federation)The state of sleep is the natural physiological state of a person that is necessary to continue life, therefore this state can be described in a work of art when characterizing the characters, especially when the dream is broken, and also in the event of dreams. Dreams in the artistic text allow the reader to penetrate into the depths of the psychic sphere of the character. In the story by A.P. Chekhov «Drama on Hunting» dreams that contain certain events and represent certain substances are associated with those phenomena that occurred in the life of the main character Zinoviev. At the same time, they describe the unreal substances and events, which, as it becomes clear later, have a prophetic character. The state of sleep, its violation, the idea of what can dream, why this dreaming occur, the characterization of sleep given by another character has to do with the inner psychological state of different characters. Thus, the reader is presented with the sphere of the unconscious, it is possible to determine the significance of this sphere in the life of the characters of the story.Key words: dream, dream of Zinov`ev, murder.DOI 10.23683/1995-0640-2017-3-170-176